2020
DOI: 10.33448/rsd-v9i10.8483
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the phenolic, antioxidant and antimicrobial potential of leaf extracts of Pereskia grandifolia Haw

Abstract: Pesquisas em Plantas Alimentícias Não Convencionais (PANC) quanto à presença de compostos bioativos e antimicrobianos são escassas e a ampliação do conhecimento a respeito de suas propriedades torna-se necessária. Neste estudo, quatro tipos diferentes de extratos (aquosos e hidroalcoólicos obtidos por refluxo e sonicação) de ora-pro-nóbis (Pereskia grandifolia Haw) foram investigados quanto à presença de compostos fenólicos, antioxidantes e antibacterianos. Os extratos de Pereksia grandifolia Haw obtidos por r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Together, the results of this research contribute to the growing evidence supporting the therapeutic potential of medicinal plants in the management of liver diseases, providing valuable insights for the development of treatments and the advancement of hepatic investigations [40][41][42]. It is important to highlight that the observed therapeutic efects can be attributed to the presence of bioactive compounds in P. grandifolia, such as phenolic compounds, favonoids and saponins, for example [43][44][45]. However, further research is necessary to identify and characterize the specifc compounds present in the extract utilized in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Together, the results of this research contribute to the growing evidence supporting the therapeutic potential of medicinal plants in the management of liver diseases, providing valuable insights for the development of treatments and the advancement of hepatic investigations [40][41][42]. It is important to highlight that the observed therapeutic efects can be attributed to the presence of bioactive compounds in P. grandifolia, such as phenolic compounds, favonoids and saponins, for example [43][44][45]. However, further research is necessary to identify and characterize the specifc compounds present in the extract utilized in this study.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the leaf mass of ora-pro-nobis has vitamins A, B and C, important for the immune process, eyes and skin (Vicente et al, 2020;Francelin et al, 2021). The absence of foliar toxicity makes it an important and useful food (Almeida-Filho and Cambraia, 1974), characterizing a complementary source in the diet of many Brazilians (Almeida et al, 2014;Takeiti et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is rich in soluble fiber, important for the digestive and intestinal process. It contains vitamins A, B and C, important for the immune process, eyes and skin, in addition to minerals, such as iron, calcium and phosphorus (Vicente et al, 2020;Francelin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cytotoxic effects on cancer and normal cell lines [8,9,49,67,68], anti-inflammatory activity [11], and cholinergic enzyme inhibitory capacity [36] have also been investigated. Aqueous and hydroalcoholic extracts of P. grandifolia leaves had their antibacterial activity tested against S. aureus and P. aeruginosa [69], and the authors found that extracts showed inhibitory activity against the tested bacteria. However, only the hydroalcoholic extract obtained by reflux was bactericidal at the tested concentrations.…”
Section: Extraction Of the Bioactives Of P Aculeata And P Grandifoliamentioning
confidence: 99%